Process Development for Bio-butanol Steam Reforming for PEMFC Application - Patel, Ronak; Patel, Sanjay (International Journal of Engineering and Technology, 2018)
In current study, process has been developed for hydrogen production from bio-butanol via steam reforming (SR) for proton exchange membrane fuel cell (PEMFC) application. Heat integration with pinch analysis method was carried out to reduce overall heating and cooling utility requirement of energy intensive SR process. Despite of highly endothermic nature of bio-butanol SR, process found to be self-sustained in terms of requirement of heating utility. Heat integrated process for hydrogen production from bio-butanol SR was found to be green process, which can be explored for its hydrogen production capacity. Â